2019
DOI: 10.15302/j-laf-1-020013
|View full text |Cite
|
Sign up to set email alerts
|

Study of Urban Greenway Planning Based on Multi-Source Data Analysis of Spatial Potential and User Behaviors — The Greenway Route Planning of Haidian District, Beijing

Abstract: Multi-dimensional collaborative development of the ecological space of Beijing-Tianjin-Hebei region and Peri-capital ecological spatial pattern optimization and implementation strategy, the World-Class Discipline Construction and Characteristic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…To achieve carbon peaking and carbon neutrality goals it is essential to provide cyclists with a bicycle-oriented urban environment. Existing research showed that a good cycling environment will make residents more inclined to choose bicycle travel (Chen, 2018(Chen, , 2019Dai et al, 2010). Bornstein and Davis (2014)'s research mentioned that "cycling environment" includes natural environment, social environment and built environment.…”
Section: Implication For Low-carbon Cycling Environment Planningmentioning
confidence: 99%
“…To achieve carbon peaking and carbon neutrality goals it is essential to provide cyclists with a bicycle-oriented urban environment. Existing research showed that a good cycling environment will make residents more inclined to choose bicycle travel (Chen, 2018(Chen, , 2019Dai et al, 2010). Bornstein and Davis (2014)'s research mentioned that "cycling environment" includes natural environment, social environment and built environment.…”
Section: Implication For Low-carbon Cycling Environment Planningmentioning
confidence: 99%
“…At this stage, most of the greenway selection is carried out by constructing a s ity evaluation model, and the science and completeness of the selection element evaluation model is an important basis for the study. In order to scientifically an tively identify the factors influencing the suitability of urban greenway selection, per obtained 57 papers on the topic of "greenway selection" based on CNKI datab cording to the statistical method of literature information, among which 17 pape on the topic of "selection suitability evaluation" [11][12][13][14]16,17,20,25,[30][31][32][33][34][35][36][37][38]. The con the route suitability evaluation system in these 17 papers was studied, and the fre of specific factors was calculated by combining synonyms of the influencing fac obtain the set of influencing factors of urban greenway route selection (as Table cording to the landscape gardening planning and design ideas, combined with th ciple of "systematic continuity" in the "Guidelines for Greenway Planning and D the main line continuity (the degree of tandem with existing greenways) and the of existing greenways that can be directly used were selected as the influencing fa the study of the suitability of urban greenway selection.…”
Section: Evaluation Model Construction Of Urban Greenway Selection Po...mentioning
confidence: 99%
“…At this stage, most of the greenway selection is carried out by constructing a suitability evaluation model, and the science and completeness of the selection elements in the evaluation model is an important basis for the study. In order to scientifically and effectively identify the factors influencing the suitability of urban greenway selection, this paper obtained 57 papers on the topic of "greenway selection" based on CNKI database according to the statistical method of literature information, among which 17 papers were on the topic of "selection suitability evaluation" [11][12][13][14]16,17,20,25,[30][31][32][33][34][35][36][37][38]. The content of the route suitability evaluation system in these 17 papers was studied, and the frequency of specific factors was calculated by combining synonyms of the influencing factors to obtain the set of influencing factors of urban greenway route selection (as Table 1).…”
Section: Evaluation Model Construction Of Urban Greenway Selection Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…Others believe that the factors affecting the supply of rural PG are analyzed from the four levels of individuals, families, villages, and regions above the village level [3,4]. In addition, some people said that local public products are connected with national public products and have characteristics that other types of public products do not have [5,6]. erefore, this article intends to use DM technology to analyze the gap between UR PG and provide solutions to narrow the gap between UR areas.…”
Section: Introductionmentioning
confidence: 99%